IMPLEMENTASI E-CRM UNTUK MENINGKAT PENJUALAN OBAT-OBATAN DAN PUPUK DI UD. MENARA TANI KECAMATAN SIMPANG EMPAT - Sri Nurainun Siahaan; Iqbal Kamil Siregar; Chitra Latiffani (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Menara Tani Simpang Empat District has not received maximum customers. Therefore, the owner is required to find more new customers than before and keep old customers by providing the latest information and maintaining good communication. Then, after the development of the business of selling drugs and fertilizers, it is certain that the level of business competition becomes stronger so that entrepreneurs must think of new strategies to improve sales quality, retain consumers and marketing to manage their customers, increase new customers and retain old customers. In line with the current development of technology and social media, various efforts have been made to increase sales. One way that a store can do to be able to compete in the world of business sales is to implement a system or method, namely CRM (Customer Relationship Management). Customer Relationship Management (CRM) is a strategy to maintain good relationships with customers, both new and old customers. Companies must also know how to win customers' hearts by prioritizing customer satisfaction, such as providing all the latest information about plants as well as by providing the best service for customers.